Circulating Adipokine Levels in Nonobese Women With Polycystic Ovary Syndrome and in Nonobese Control Women: A Systematic Review and Meta-Analysis - Lin, Kainan; Sun, Xiaoting; Wang, Xiao; Wang, Hanchu; Chen, Xia (Frontiers in Endocrinology, 2021)
Concentrations of circulating adipokines in non-obese PCOS patients had been reported in many researches, however, these results were conflicting. The aim of this meta-analysis was to assess whether the levels of circulating adipokines were changed in non-obese polycystic ovary syndrome (PCOS). To identify eligible studies, literature research was performed in the database of PubMed, Embase, Web of Science without the restriction of region, publication or language. Of the total studies found, only 81 met the inclusion criteria. The meta-analysis showed that circulating levels of adiponectin [-0.95 (95% CI, -1.36 to -0.53)] decreased statistically in non-obese PCOS women. On the contrary, circulating levels of chemerin [1.13 (95% CI, 0.08 to 2.18)], leptin [0.47 (95% CI, 0.13 to 0.81)], resistin [0.45 (95% CI, 0.03 to 0.88)] and visfatin [1.38 (95% CI, 0.68 to 2.09)] increased significantly in non-obese PCOS females. Besides, there was no statistically significant change in the circulating levels of apelin [0.32 (95% CI, -1.34 to 1.99), irisin [1.01(95% CI, -0.68 to 2.70), omentin [-0.37(95% CI, -1.05 to 0.31)] and vaspin [0.09(95% CI, -0.14 to 0.32)] in non-obese PCOS patients. Scientific evidence suggested that the levels of circulating adipokines altered in non-obese PCOS patients compared with controls. Independent of the degree of obesity, the abnormal change of circulating adipokines levels might play an important role in the occurrence and development of PCOS.